Analyzing Translation Errors of Trainee Translators: A Case Study on Tourism Promotional Material. - Erkırtay, Olcay Şener (Çankaya University Journal of Humanities & Social Sciences, 2024)
The present study aims to scrutinize the trainee translators' errors in their translations of tourism promotional material, a brochure, from Turkish into English. Thus, this study is designed as a descriptive qualitative research and corroborated with quantitative analysis, presenting a thorough analysis of the translated texts based on the American Translators Association (ATA) translation error taxonomy. The framework of this study employs Corder's taxonomy of phases for error analysis, namely, selection of a text, identification of errors, classification of errors, and explanation of possible reasons for those errors. The data discussed in this paper derive from the translated texts of fiifteen trainee translators i.e., third- and fourthyear T&I students at a private university enrolled in the Cultural Aspects of Translation and Interpretation course. The results revealed a statistical difference between the main error categories. According to the fiindings, trainee translators made most errors in the form of the language, i.e. target language mechanics, followed by errors in meaning and errors in writing quality. In acting as a "cultural mediator" in tourism text translations, trainees have also been found to be not so effective as they are supposed to be. With the results unfolded, it is hoped to benefiit to both translation professors and trainees themselves.